2013
DOI: 10.1186/1472-6831-13-5
|View full text |Cite
|
Sign up to set email alerts
|

Supragingival plaque microbial analysis in reflection to caries experience

Abstract: BackgroundDental caries develops as a result of the metabolism of carbohydrates by cariogenic bacteria present in a complex biofilm. The present study aimed to examine if bacteria in pooled supragingival plaque samples quantified using a “checkerboard DNA-DNA hybridization” based panel of caries-related bacteria, could reflect the caries experience in a manner similar to saliva samples analysed using a chair-side method in a previous investigation.MethodsA total of 86 mothers and their children aged 4–6 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 20 publications
1
16
0
3
Order By: Relevance
“…Thus, these three species of Lactobacillus have been also reported in the childhood caries when the plaque samples had cultured anaerobically on the blood agar medium 11,76 . Some recent studies conformed Table 3 that the L. casei and L. gasseri predominant in childhood caries, L. fermentum and L. salivarius are more frequently found in dental plaque samples in adults 46,77,78,119 . 72 Aas et al, 74 Gross et al, 75 Tanner et al, 76 Mannaa et al, 77 Shimada et al, 46 Richards et al,…”
Section: Tennpaisan and Dahlen (2006) 56mentioning
confidence: 57%
“…Thus, these three species of Lactobacillus have been also reported in the childhood caries when the plaque samples had cultured anaerobically on the blood agar medium 11,76 . Some recent studies conformed Table 3 that the L. casei and L. gasseri predominant in childhood caries, L. fermentum and L. salivarius are more frequently found in dental plaque samples in adults 46,77,78,119 . 72 Aas et al, 74 Gross et al, 75 Tanner et al, 76 Mannaa et al, 77 Shimada et al, 46 Richards et al,…”
Section: Tennpaisan and Dahlen (2006) 56mentioning
confidence: 57%
“…These differences between bacteria species have played a role in oral diseases, which cannot be ignored. The increase in Firmicutes has been confirmed as being closely related to dental caries in many studies [ 20 , 25 , 28 , 29 ], Streptococcus are Gram-positive bacteria and are often presented in the supragingival plaque; they are associated with the occurrence of dental caries [ 30 , 31 ]. Porphyromonas species is a Gram-negative bacterium that is often found in the subgingival plaque and is often associated with periodontal disease [ 8 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…This finding may explain the fact that there was no significant increase in the number of DMFS at T2 compared to T1 for both the G- and P-groups although the plaque index was significantly less at T2. Mannaa et al showed that no significant relationships between the bacterial counts pooled from dental plaque and the caries experience (Mannaa et al, 2013). Moreover, the reason of having no significant difference in number of MS and LB over time could be explained by a study performed by Peros et al (2011), showing that the period from the 6th to 12th week of orthodontic therapy is the peak time for intensive intraoral growth of MS and LB; the amount of MS and LB decreased afterward, which support our findings as we collected the saliva for MS and LB at de-bonding i.e.…”
Section: Discussionmentioning
confidence: 99%